2002
DOI: 10.1186/1471-2431-2-7
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and molecular spectrum of galactosemia in patients from the Cape Town region of South Africa

Abstract: BackgroundThe objective of this study was to document the clinical, laboratory and genetic features of galactosemia in patients from the Cape Town metropolitan region.MethodsDiagnoses were based on thin layer chromatography for galactosuria/galactosemia and assays of erythrocyte galactose-1-phosphate uridyltransferase (GALT) and galactokinase activities. Patients were screened for the common S135L and Q188R transferase gene mutations, using PCR-based assays. Screening for the S135L mutation in black newborns w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
2
39
1
4
Order By: Relevance
“…The ages at the time of diagnosis were examined in many studies, and patients who were diagnosed in the first 15 days were defined as early diagnosed (8)(9)(10)(11)(12). In our study, six of our patients were diagnosed in the first 15 days after birth and the remaining eight patients were diagnosed after 15 days.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ages at the time of diagnosis were examined in many studies, and patients who were diagnosed in the first 15 days were defined as early diagnosed (8)(9)(10)(11)(12). In our study, six of our patients were diagnosed in the first 15 days after birth and the remaining eight patients were diagnosed after 15 days.…”
Section: Discussionmentioning
confidence: 90%
“…In the study conducted by Karadağ et al (8), it was reported that the mean age at the time of hospital presentation was 13 days. Henderson et al (9) reported that 17 patients were diagnosed over a period of 21 years in the region of Cape Town in South Africa, the mean age at the time of diagnosis was 5.1 months. In the study conducted by Krantz et al (10) with 148 patients between 1955 and 1995 in Germany, the rate of early diagnosis was reported as 57.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation c.855G>T (p.K285N) accounts for a majority of CG patient alleles in Eastern Europe (Lukac-Bajalo et al 2007). Finally, c.404C>T (p.S135L) accounts for a majority of CG patient alleles in parts of Africa (Henderson et al 2002). Other mutations, such as c.584T>C (p.L195P), are less common, accounting for only a small percentage of reported patient alleles, and yet others are "private" -reported only in one affected patient or family.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous are carrier because they inherit one normal gene and one defective gene. (4) Narendra Rathi et al observed that three congenital disorders are related to galactose metabolism -a) type one galactosemia (classic galactosemia) -deficiency of GALT (galactose -1-phosphate uridyl transferase) b) type two galactosemia -deficiency of galactokinase. It solely presents with cataract .…”
Section: Introductionmentioning
confidence: 99%